ChemInform Abstract: A General, Regiospecific Synthetic Route to Perfluoroalkylated Arenes via Arenediazonium Salts with RFCu(CH3CN) Complexes. Issue 12 (March 2015) - Jiang, Dong‐Fang; Liu, Chao; Guo, Yong; Xiao, Ji‐Chang; Chen, Qing‐Yun
Abstract Arylamines can be converted into perfluoroalkylated arenes (III) under mild conditions.